Assessing Students’ Pronunciation Skills and How to Improve Them - Muhammad Amin; Thalia Qaulan Tsaqiila (Indonesian Journal of Teacher Education, 2023)
Phonetics and phonology, in one way or another, are related to pronunciation. Despite the still inconclusive research results on how much one’s knowledge of phonetics and phonology will affect one’s pronunciation, in teaching and learning contexts it is still considered relevant to assess students’ spoken language abilities using the phonetic and phonological approach. This study was qualitative in nature and intended to collect information on the verbal language performance of two English as a Foreign Language (EFL) speakers, each of whom speaks Indonesian and one local language.